Role of genetic variation in the transcriptional inhibitor protein Smad6 in the predisposition to congenital cardiovascular malformation. (22nd September 2015) - Tan, HL; Topf, A; Griffin, H; Palomino Doza, J; Hall, D; Hussain, R; Eden, J; Rahman, T; Cunnington, M; Goodship, J; Keavney, B
Abstract : Introduction: Bone morphogenetic proteins (BMP) regulate many biological processes during development, including cardiac development. BMP belong to the transforming growth factor beta superfamily. BMP are produced as inactive precursor proteins, which then undergo endoproteolytic cleavage and dimerisation to yield active BMP. Activated BMP bind to type I and type II receptors. Formation of the complex induces type II receptors to phosphorylate the type I receptor, which in turn phosphorylates receptor-activated Smad (R-Smad) proteins. The activated Smad binds to common Smad4 upon which the complexes are translocated to the nucleus and participate in transcription. Smad6 functions as an inhibitory Smad by competing with R-Smad for interaction with the activated type I receptor or by competing with Smad4 for complex formation with the phosphorylated Smad1. Functional studies of Smad6 knockout mice showed cardiac defects, while Smad6 was expressed strongly in the heart throughout development in the chick. Methods: The coding regions of Smad6 of 92 patients diagnosed with congenital cardiovascular malformation were sequenced on the MegaBACE platform by capillary electrophoresis and were examined using GAP4 software to screen for novel mutations potentially predisposing to cardiogenic malformation. A total of 1000 control chromosomes were genotyped for the previously unreported genetic variants using the SEQUENOM platform and TaqMan probes. The presence or absence of the novel genetic variants in the controls was recorded. Bioinformatic analyses to determine the likely functional effects of the identified changes were performed. Results: Ten previously unreported genetic variants were identified by sequencing; four of these were absent in healthy controls. The features of identified variants are summarised in the table. Of these novel variants, seven were in untranslated regions and one was in an intron. At 2274C/T, residue number 237, a synonymous substitution (histidine to histidine) occurred. This change, however, altered an exonic splice enhancer site. A non-synonymous genetic variant was found at 79800 G/T, residue number 484; this resulted in a cysteine to phenylalanine change, which is predicted to be deleterious to protein function by SIFT and polyphen programmes (see Abstract 101 Figure 1. figs 1 and 2 ). Conclusions: We have found genetic variants in Smad6 that appear to be involved in susceptibility to congenital cardiovascular malformation. Functional analysis of 79800G/T will be performed to study the effect on splicing or on protein activity and interaction with other members of the BMP signalling pathway to evaluate the effects of the mutations during heart development. This study suggests that dysregulation of BMP signalling may be an important factor in cardiovascular malformation; similar sequencing studies of other components of the BMP signalling pathway are in progress.